Mesenchymal Stem Cells Enhance Pulmonary Antimicrobial Immunity and Prevent Following Bacterial Infection - Wenchao Li; Weiwei Chen; Saisai Huang; Xiaojun Tang; Genhong Yao; Lingyun Sun (Stem Cells International)
Background. Immunosuppressants such as cyclophosphamide (CTX) have been employed to treat a wide array of autoimmune diseases. The most unfavourable side effects of these drugs are their suppression on the antimicrobial immunity and increasing the risk of infection. As a promising substitution/adjunct, mesenchymal stem cells (MSCs) are currently being tested in several clinical trials. However, their influence on the recipients’ antimicrobial immunity remains unclear. Methods. In this study, C57BL/6 mice were treated with either CTX or MSCs, and then both the innate and adaptive immunity of the lung were determined. To investigate the influence of CTX and MSCs on the immune defence against infection, the treated mice were intranasally infected with opportunistic pathogen Haemophilus influenzae (Hi). Bacterial clearance and antibacterial immune responses were analysed. Results. Our data showed that CTX strongly inhibited the proliferation of lung immune cells, including alveolar macrophages (AMs) and T cells, whereas MSCs increased the numbers of these cells. CTX suppressed the phagocytic activity of AMs; on the contrary, MSCs enhanced it. Notably, infusion of MSCs led to a remarkable increase of regulatory T cells and Th1 cells in the lung. When infected by Hi, CTX did not significantly impair the elimination of invaded bacteria. However, MSC-treated mice exhibited accelerated bacterial clearance and moderate inflammation and tissue damage. Conclusion. Our study reported that unlike traditional immunosuppressants, modulation of MSCs on the recipient’s immune response is more elegant. It could preserve and even enhance the antimicrobial defence, suggesting that MSCs are better choice for patients with high risk of infection or those who need long-term immunosuppressive regimen.